Cross-sectional observational study of the sleep disorders in subjects assisted in the Basic Health Units and Family Health Program in Divinopolis, Brazil – a protocol study - Pasqualotto, Luísa Teixeira; Santos, Walquíria da Mata; Santos, Cíntia Aparecida; Camilo, Ingrid Jordana Silva; Faria, Marcos Eugenio Mattos Rocha; Alves, Jacqueline; Seixas, Marco Tulio Tavares; Silva, Rogerio Júnior Esteves e; Santana, Caroline Alvarenga de Assis; Júnior, Newton Santos de Faria (Manual Therapy, Posturology & Rehabilitation Journal, 2017)
Introduction: Sleep disorders have a high prevalence in the general population being currently considered as a major public health problem. In the last four decades, scientific interest in sleep patterns has steadily grown. Such studies may contribute to a better understanding of the clinical course to explore potential therapeutic interventions. This study will aim to verify the prevalence of sleep disorders in subjects assisted at the Basic Health Units (UBS’s) and Family Health Program (PSF’s) in Divinópolis, MG, Brazil. Methods: This research will be an observational, cross-sectional study carried out by professors and students from the University of State of Minas Gerais - UEMG, Divinópolis Unit, with subjects recruited from the UBS’s and PSF’s in Divinópolis-MG, between March 2016 and December 2017. These subjects will be assessed clinically and respond to the Pittsburgh Sleep Quality Index (PSQI), Epworth Sleepiness Scale (ESS), Berlin Questionnaire, SF-36 Quality of Life Questionnaire, evaluating the quality of sleep, presence of sleep disorders, excessive daytime sleepiness, risk for obstructive sleep apnea and quality of life. Discussion: Recently, sleep disorders were considered a global public health problem, affecting the quality of life of the population and influencing morbidity and mortality. The results of epidemiological studies are not only applicable in clinical practice but also in the planning and implementation of public policies and programs aimed at controlling sleep disorders and their impact on individuals and societies.